COVID-19 contact tracing apps: UK public perceptions. Issue 1 (1st January 2022) - Samuel, G.; Roberts, S. L.; Fiske, A.; Lucivero, F.; McLennan, S.; Phillips, A.; Hayes, S.; Johnson, S. B.
ABSTRACT: In order to combat the COVID-19 pandemic, policymakers around the globe have increasingly invested in digital health technologies to support the 'test, track and trace' approach of containing the spread of the novel coronavirus. These technologies include mobile 'contact tracing' applications (apps), which can trace individuals likely to have come into contact with those who have reported symptoms or tested positive for the virus and request that they self-isolate. This paper takes a critical public health perspective that advocates for 'genuine participation' in public health interventions and emphasises the need to take citizen's knowledge into account during public health decision-making. In doing so, it presents and discusses the findings of a UK interview study that explored public views on the possibility of using a COVID-19 contact-tracing app public health intervention at the time the United Kingdom (UK) Government announced their decision to develop such a technology. Findings illustrated interviewees' range and degree of understandings, misconceptions, and concerns about the possibility of using an app. In particular, concerns about privacy and surveillance predominated. Interviewees associated these concerns much more broadly than health by identifying with pre-existent British national narratives associated with individual liberty and autonomy. In extending and contributing to ongoing sociological research with public health, we argue that understanding and responding to these matters is vital, and that our findings demonstrate the need for a forward-looking, anticipatory strategy for public engagement as part of the responsible innovation of the COVID-19 contact-tracing app in the UK.